KAJIAN SEMIOTIKA PADA PUISI EMBRIO, LELAKIKU, DAN SPORA KARYA OKA RUSMINI - Lulu Lutfianingrum; Iqbal Sidik; Dian Hartati (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Poetry is a depiction of meaning through a process of contemplation and imaginative experience then arranged in the form of words so that the reader can feel the meaning conveyed by the poet through writing. The study of poetry through the realm of semiotics is more interesting because this study discusses how to study a poem by enjoying the markers that are built into a work with the beauty of language. This study was also structured with the aim of enriching the reader's knowledge by dissecting the semiotics contained in the poems "Embrio", "Lelakiku", and "Spora" by Oka Rusmini. The method used in this research is descriptive qualitative method. This study uses the semiotic approach of Aart Van Zoest. The poem "Embrio" consists of ten sentences, the poem "Lelakiku" consists of sixteen sentences, and the poem "Spora" consists of twenty-five sentences. Sentences in these poems use more incomplete sentence patterns than complete sentence patterns. The three poems are dominated by connotative sentences and there are six figure of speech, namely metaphorical figure of speech, personification figure of speech, hyperbole figure of speech, euphemism figure of speech, tautological figure of speech, and allegorical figure of speech spread over several sentences. Six isotopes were found, including movement isotopes, natural isotopes, human isotopes, hearing perception isotopes, visual perception isotopes and organ isotopes. I think the lyrics in these three poems are dominated by the point of view of women who feel pain, fatigue, and anxiety from a child. Keywords: Poetry, Semiotics, Oka Rusmini.